Anna's heaven - Hole, Stian 1969- (Eerdmans Books for Young Readers, 2014)
After the death of her mother, Anna and her father imagine that Heaven might be a place where one can help in God's garden, visit with old friends, and take off one's socks whenever one pleases
Keywords: Heaven; Future life; Fathers and daughters; Death; Imagination; Trauerarbeit; Fantasie; Tochter; Glaube; Fantasiereise; Philosophie; Vater; Mutter; Naturerlebnis; Tod; Bilderbuch